Powerplays how teens can pull the plug on sexual harassment - Hodgson, Harriet W. (Minneapolis, Minn. Deaconess Press, 1993)
Explains how teenagers can identify, fight, and prevent sexual harassment in school and on their jobs, stressing how inaction may sometimes lead to sexual abuse.
Includes bibliographical references and index.
UCWS-3098g donated by Dr. Thelma B. Kintanar - July 2017
Keywords: Sexual harassment -- United States -- Juvenile literature; Sexual harassment -- United States -- Prevention -- Juvenile literature; Child sexual abuse -- Prevention